Stigma and discrimination faced by adolescents living with HIV and experiencing depression in Malawi - Maria Faidas; Melissa A. Stockton; Steven M. Mphonda; Griffin Sansbury; Haley Hedrick; Jackson Devadas; Twambilile Phanga; Laura Ruegsegger; Jack Kramer; Hillary Mortensen; Kazione Kulisewa; Brian W. Pence; et al. (BMC, 2024)
Abstract Background In Malawi, approximately 25% of adolescents living with HIV (ALWH) also suffer from depression. Not only is HIV stigma a major contributor to depression but it also adversely impacts HIV care engagement. ALWH can experience HIV stigma as stereotyping, social exclusion, low social support, and abuse, and these experiences are associated with poor mental health. Despite recognition of the deleterious effects of HIV stigma, we have limited knowledge of how stigma is experienced by ALWH with comorbid depression. Guided by the Health Stigma and Discrimination Framework, we describe stigma faced by ALWH and comorbid depression in Malawi and its implications for future interventions. Methods As part of a larger formative study to adapt a mental health counseling intervention, we conducted in-depth interviews, social support mapping sessions, and focus-group discussions with 25 ALWH, 4 caregivers of ALWH, 3 HIV providers, and 5 participants and 5 staff of a prior mental health counseling intervention. After analyzing the stigma codes, we used the Health Stigma and Discrimination Framework to organize the data into four key domains: drivers, manifestations, outcomes, and health and social impacts. Results Major drivers of HIV stigma included fear of HIV transmission, negative effects of antiretroviral therapy (ART), association with death, inaccurate knowledge, and negative attitudes towards ALWH. The most common manifestations of HIV stigma were gossip, insults and mocking, and physical and social distancing. Decreased ART adherence and missed HIV appointments were commonly cited outcomes of HIV stigma. Broader health impacts of HIV stigma were notable for mental health comorbidities including depression, anxiety, substance use, and suicidality. Identified resilience strategies included support for HIV care engagement and psychosocial support from family and friends. Conclusions This study systematically describes the stigmatization process faced by ALWH and experiencing depressive symptoms in Malawi. Notably, HIV stigma continues to disrupt HIV care and detrimentally impacts mental health during adolescent development. Further studies focused specifically on stigma are needed to better characterize this process and identify additional resilience factors. Investment in stigma-reduction interventions for ALWH is needed to avert poor mental health and HIV outcomes.